Environmental Health Perspectives in Electronic Cigarette Use: A Sustainable Approach (2016)
A review is carried out on environmental health perspectives in electronic cigarettes using a sustainable approach. Electronic cigarette (EC) use continues to increase with time from its first introduction in 2004 and could have either deleterious or beneficial effects on public health depending on its impact on smoking initiation and cessation. Previous reports have described conditions of EC use that support minimal or no nicotine delivery as a placebo for tobacco use cessation. This review underscores the need for effective surveillance of e-cigarettes and their effects on smoking, users’ health and a smoke-free policy. Keywords: Electronic cigarette, public health, nicotine, cigarette.